TINJAUAN YURIDIS PENURUNAN SANKSI PIDANA PENJARA TINDAK PIDANA KORUPSI DALAM UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Fadia Inayah Putri; Mukhlis R; Tengku A. Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Corruption has been considered a phenomenon that is difficult to overcome inthe history of the Indonesian nation, so there should be no compromise whatsoeverwith corruption. Indonesia should apply the Zero Tolerance principle forcorruptors. In the new Criminal Code which was passed into law on January 12023, there are significant changes regarding the specific minimum threat ofimprisonment for criminal acts of corruption. This threat is regulated in Article603, which is an improvement on Article 2 paragraph (1) of the CorruptionEradication Law which was previously in force. The minimum threat stipulated inArticle 603 turns out to be lower than that stated in the previous regulations,especially in Article 2 paragraph (1), which is the mainstay article in prosecutingcorruption cases.This research is classified as a normative juridical research type. The dataused is primary data and secondary data consisting of primary legal materials,secondary legal materials and tertiary legal materials. The data collectiontechnique uses the literature review method, namely presenting and analyzing datafrom several sources such as laws, draft laws, books and opinions of criminal lawexperts. This research was then analyzed descriptively qualitatively. The conclusiondrawing technique used is a deductive mindset.The results of this research are that the threat of minimum criminalsanctions for perpetrators of corruption is lighter, motivated by a change in theparadigm for eradicating corruption. Corruption perpetrators should not besubject to high prison sentences, but rather with additional penalties in the form ofconfiscation of all assets of those involved in corruption crimes resulting fromcorruption crimes. This is in accordance with legal principlesIt is not expedient forthe asas to be evil, namely that the perpetrator of the crime must not enjoy theproceeds of his crime.Keywords : Corruption, State Losses, Recovery Assets